Joachim Lelewel’s Edda of 1807 - Krakow, Annet (Folia Scandinavica Posnaniensia, 2017)
This article focuses on Joachim Lelewel’s interest in Old Norse literature as reflected in his paper on Old Norse literature delivered in 1806 and his book Edda that was published a year later. Lelewel’s Edda comprises the first Polish translation (partly as a concise retelling) of selected parts of the French translation of the Poetic Edda and the Snorra Edda as included in Paul Henri Mallet’s Monumens de la mythologie [...] published in 1756. Lelewel’s work is placed in the context of the rising interest in this literature before 1800, whereby special attention is put on the sources Lelewel resorted to, in particular Mallet’s publications and articles in the French literary magazine Magasin Encyclopedique. Comparing the Eddas in Lelewel’s and Mallet’s publications, one can, among other things, note that Lelewel (1) ignores the literary value of the dialogue form in Gylfaginning due to a narrow focus on the mythological content (2) relates the migration of the Scythians to northern Europe in his introduction which thus serves as a substitute for the missing Prologue to the Snorra Edda and (3) partly deviates from Mallet in his footnotes. Aspects (2) and (3) can also be linked back to Lelewel’s use of Magasin Encyclopedique.